2022
DOI: 10.1126/sciadv.abk2039
|View full text |Cite
|
Sign up to set email alerts
|

From structure to sequence: Antibody discovery using cryoEM

Abstract: One of the rate-limiting steps in analyzing immune responses to vaccines or infections is the isolation and characterization of monoclonal antibodies. Here, we present a hybrid structural and bioinformatic approach to directly assign the heavy and light chains, identify complementarity-determining regions, and discover sequences from cryoEM density maps of serum-derived polyclonal antibodies bound to an antigen. When combined with next-generation sequencing of immune repertoires, we were able to specifically i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 58 publications
0
20
0
Order By: Relevance
“…Solving their high-resolution structures can provide useful footprints for HIV-1 vaccine design. A high-throughput antibody discovery technology has been developed by Ward et al 58 based on cryo-EM based EMPEM and high-resolution structural analysis for novel monoclonal antibody discovery that can further determine detailed structure- and sequence-based information from the pediatric and adult bnAbs of multiple-epitope specificities. Such advanced techniques have benefits over previously used high-throughput phage display technology-based HIV-1 bnAb isolation from random mutant libraries based on recombinant antibodies.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
“…Solving their high-resolution structures can provide useful footprints for HIV-1 vaccine design. A high-throughput antibody discovery technology has been developed by Ward et al 58 based on cryo-EM based EMPEM and high-resolution structural analysis for novel monoclonal antibody discovery that can further determine detailed structure- and sequence-based information from the pediatric and adult bnAbs of multiple-epitope specificities. Such advanced techniques have benefits over previously used high-throughput phage display technology-based HIV-1 bnAb isolation from random mutant libraries based on recombinant antibodies.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
“…Shortening the screening and structure optimization time of highly efficient antibodies is a long-term goal of antibody development strategies. A recent study reported that the combination of cryo-EM and next-generation sequencing can quickly obtain key epitope information without isolating monoclonal antibodies, greatly shortening the time for antibody development [ 98 ]. The main process is shown in Fig.…”
Section: Application Of Cryo-em In Antibody Drug Developmentmentioning
confidence: 99%
“…EM-based polyclonal epitope mapping (EMPEM) is a tool for rapid and comprehensive structural analysis of immune complexes featuring vaccine-elicited polyclonal antibodies (pAbs) purified from sera ( 9–12 ). Additionally, we have recently shown that structural information from the reconstructed high-resolution maps can be used to identify sequences of polyclonal antibody families ( 13 ). EMPEM has thus far been only applied to recombinantly produced minimal antigens.…”
Section: Introductionmentioning
confidence: 99%